lim x^3 -3x+2 / x^2 - 1 , com x tendendo 1
Soluções para a tarefa
Respondido por
0
.
Ola Jm
(x³ - 3x + 2)/((x - 1)*(x + 1)) = /x - 1)²*(x + 2)/(x + 1)*(x - 1)
= (x - 1)*(x + 2)/(x + 1)
lim⇒x=1 ⇒ (1 - 1)*(1 + 2)//1 + 1) = 0
.
Ola Jm
(x³ - 3x + 2)/((x - 1)*(x + 1)) = /x - 1)²*(x + 2)/(x + 1)*(x - 1)
= (x - 1)*(x + 2)/(x + 1)
lim⇒x=1 ⇒ (1 - 1)*(1 + 2)//1 + 1) = 0
.
Perguntas interessantes
Geografia,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Geografia,
1 ano atrás